Effect of Sales Growth, Liquidity, Profitability And Operating Cash Flow on Financial Distress In Food And Beverage Subsector Listed on IDX - Aini, Rahmatul; Wijaya, M Rizky; Adam, Aisyah Azhar (Husnayain Business Review, 2025)
The purpose of this study is to ascertain how financial hardship is impacted by sales growth, liquidity, profitability, and operating cash flow in manufacturing firms in the food and beverage subsector that are listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024. This study's methodology is quantitative research. 43 food and beverage firms that were listed on the Indonesia Stock Exchange between 2020 and 2024 made up the study's population, and ten companies served as samples. Binary Logistic Regression is used in the data analysis method by SPSS 27. The study's findings indicate that financial distress is influenced by liquidity. Financial suffering is unaffected by operating cash flow, sales growth, or profitability.